The arteries originating from the aortic arch and the branches of these arteries in red squirrels (Sciurus vulgaris) - Aydin, A. (Czech Academy Agricultural Sciences, 2011)
This study had the aim of investigating the anatomy of the aortic arch in squirrels (Sciurus vulgaris). Ten squirrels were studied. The materials were carefully dissected and the arterial patterns of arteries originating from the aortic arch were examined. The brachiocephalic trunk and the left subclavian artery were detached from the aortic arch. The brachiocephalic trunk first gave the left common carotid artery, and then detached to the right subclavian and common carotid artery. In all the examined materials, the left and right subclavian arteries gave branches that were similar after leaving the thoracic cavity from the cranial thoracic entrance. But while the whole branches of the the right subclavian artery were arising from almost the same point the left subclavian artery gave these branches in a definite order, and the branches that separated were the following: the internal thoracic artery, the intercostal suprema artery, the ramus spinalis, the vertebral artery and the descending scapular artery. It also gave the common branch formed by the junction of three of the cervical superficial, the cevical profund and the suprascapular arteries. After the separation of these branches, continuation of the artery gave the external thoracic artery on the external face of the thoracic cavity and then formed the axillar artery. The axillary artery separated into the subscapular and the brachial arteries. Thus, the arteries originating from the aortic arch and the branches of these arteries are different from other rodents and from domestic mammals.
Keywords: arteries; aortic arch; red squirrel (Sciurus vulgaris)